Analisis Pengelolaan Aset Lembang : (Studi Kasus: Lembang Tondon Matallo, Kecamatan Tondon, Kabupaten Toraja Utara) - Yohanis Lotong Ta’dung; Westerini Lusdani; Dhea Toding Pasak (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research aims to determine the management of Village Assets in Lembang Tondon Matallo, Tondon District, North Toraja Regency. This research includes qualitative research with data collection methods using interviews, observation and documentation. The research results show that the management of Village Assets in Lembang Tondon Matallo has not been optimal. Of the series of stages in Village Asset Management, there are still several stages that have not been implemented by employees in Lembang, such as the asset security stage where there are still assets in the form of land and buildings that do not yet have land certificates because they have not been handed over. Apart from that, another Village Asset Management stage that has not been implemented by Lembang is asset write-off, where assets that have experienced depreciation and no longer have value are still recorded in the village asset report.